Internalisasi Nilai Religius dalam Novel Cinta di Ujung Sajadah Karya Asma Nadia dan Pembelajarannya di Sekolah Menengah Atas - Ratnaningsih, Dewi; Widayati, Sri; Ruchiyat, Marina Gusnia; Aprilianti, Putri (Universitas Muhammadiyah Kotabumi, 2024)
The problem in this study is the internalization of religious values ​​in Asma Nadia's novel Cinta di Ujung Sajadah and its learning in high school. The purpose of this study is to describe the religious values ​​contained in the novel Cinta di Ujung Sajadah by Asma Nadia and to describe the learning plan for the internalization of religious values ​​in high schools. The method used is descriptive with a qualitative approach. The results of the study show that there are four religious values ​​in Asma Nadia's novel Cinta di Ujung Sajadah, namely the relationship between man and God, man and himself, man and society, and man and nature. The novel Cinta di Ujung Sajadah by Asma Nadia is suitable as learning material in high schools because it meets the criteria for aspects of language, psychology, and cultural background. The teacher can internalize the religious values ​​contained in the novel to the students according to the learning steps which consist of opening, learning core, and closing.